Perceived Social Support, Academic Self-Efficacy, and Anxiety among Final Year Undergraduate Students: A Mediation Analysis - Elisabeth Dina Laksmiwati; Marselius Sampe Tondok (Kuras Institute, 2023)
Students, especially in the final year, often encounter various sources of stress and increasingly high academic demands, which have the potential to cause academic anxiety. This study aimed to determine the effect of perceived social support on academic anxiety through self-efficacy as a mediator. Employing a cross-sectional quantitative research design, this study involved a sample of 80 final-year undergraduate students, comprising 49 females and 31 males. Data were collected via an online questionnaire encompassing three scales: General Anxiety Disorder-7 (GAD-7), Academic Self-Efficacy Scale (ASES), and The Multidimensional Scale of Perceived Social Support (MSPSS). The mediation analysis results revealed that academic self-efficacy acts as a full mediator in the relationship between perceptions of social support and student anxiety. These findings highlight the potential effectiveness of interventions to bolster students' self-efficacy to mitigate the adverse effects of academic-related stressors, ultimately enhancing their overall well-being and academic performance.